ANALISIS KUALITAS PELAYANAN SIPAJAKDADI DI KABUPATEN SUMEDANG - teddy marliady nurwan; Adisty Kusdiani; Bagus Brilian; Fadhil Mahbub; Ginalia Amanda; Indra Permana (JRPA - Journal of Regional Public Administration, 2023)
The purpose of this study was to determine and analyze the quality of services using the On-site List Health Insurance Participation Service Information System (SIPAJAKDADI) at the Sumedang Regency. The research method used in this study, namely qualitative research methods. The technique of determining research informants, namely purposive sampling. With research informants, namely 1 Social Worker Functional person, 1 Social Service Analyst, 1 District Operator, 1 SIPAJAKDADI Operator. The data collection techniques used are literature studies and field studies consisting of observations, interviews, and documentation studies. Meanwhile, the data processing procedures in this study are data reduction, display data, conclusion drawing / verification data and triangulation. Based on the results of the study, it was concluded that the quality of service using SIPAJAKDADI in the process of participating in the PBI JK APBD participation service at the Social Service Office has been maximized, but there are still several factors that hinder employees from improving PBI JK participation services, namely poor networks, disruptions to the server, socialization and technical guidance that has not been maximized, and employees who are still lacking. The efforts made by social service employees in improving PBI JK participation services are by increasing internet network access speeds and increasing hosting capacity on servers so that they can be accessed simultaneously by many users, socializing to the public so that services are optimal, making policies regarding the provisions of operators who have followed bimtek, carrying out special training for employees who have not mastered deeply, and the provision of SIPAJAKDADI access to every village /kelurahan in Sumedang Regency for faster service.